Program Kampung Keluarga Berkualitas di Kalurahan Condongcatur Kapanewon Depok - Ari Susanti; R. Widodo Triputro (CV. Ulil Albab Corp, 2023)
Condongcatur KB Village was established in 2019. The main problem faced by Condongcatur KB Village is related to the absence of an activity fund budget. The source of financing for activities only relies on ADD and community self-help. This study aims to describe the effectiveness and benefits of the KB village program in realizing quality family formation in Condongcatur Village. This research is a descriptive qualitative research with a case study approach. The selection of informants was carried out using a purposive technique. Informants in this study include: Head of the KKB Program Working Group, PLKB Kapanewon Depok, Working Group Members, Residents, Lurah, Head of LPMK, Head of BPKAL, and Kamituwo of Condongcatur Village. The results showed that the KB Village Program has been effective in achieving the goal of forming a quality family, supported by various elements of the community and related parties. The benefits of this program include reducing population growth and controlling migration, increasing family awareness of family planning, strengthening family relationships and with the environment, providing support to face economic, social, and health challenges, improving economic welfare through training, creating an environment that supports optimal growth, encouraging environmental awareness, and improving access and quality of education through Community Learning Hours.